Key concepts in modern Indian studies - Dharampal, Gita; Dwyer, Rachel; Kirloskar-Steinbach, Monika; Phalkey, Jahnavi (O. U. P, 2015)
Modern Indian studies have become a site for new, creative, and thought-provoking debates extending over a broad canvas of crucial issues. As a result of socio-political transformations, certain concepts such as Ahimsa, Caste, Darshan, and Race have taken on different meanings.